(untitled) - Karl Max (1816-1883) (New York, 1992)
The book begins with Max's theory and its philosophical and political limitations. In part 2, the book describes how Marxism was expressed in the theory and practice of the socialist and communist movements between 1880 and 1935. The movements were the "betrayal" of the original vision of Marxism, although they also point up some crucial weaknesses in the theory itself. Part 3 presents two essential elements of "rebirth" of Marxism: Western Marxism and socialist feminism. These perspectives retain the original Marxist vision of a classless, rational, and emancipating society. Part 4 examines some contemporary concerns, updates Marxist analysis of present-day capitalist economic and political life, contains examples of ongoing debates concerning the relation between Marxism and other radical perspectives
Keywords: communism - history,marx, karl, 1816-1883 - influence,socialism - history